2021
DOI: 10.1186/s12348-020-00232-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of Penicillin results in therapeutic intravitreal levels in chronic postoperative endophthalmitis

Abstract: Importance The role of systemic antibiotics in the treatment of bacterial endophthalmitis remains controversial. While penicillin is a highly effective antibiotic against bacteria that frequently cause endophthalmitis, the ability of systemically administered Penicillin G to penetrate into the vitreous at adequate therapeutic concentrations has not been studied. Its role in the treatment of endophthalmitis, particularly for bacteria for which it is the antibiotic of choice, therefore remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Fukuda and colleagues reported that dupilumab was effective in treating giant papillae on the palpebral conjunctiva of two patients with atopic keratoconjunctivitis, and as such, they suggested the potential benefits of using dupilumab as an immunobiologic agent in individuals with severe forms of chronic ocular allergy [ 192 ]. However, there have been reports of dupilumab-associated ocular surface disease in patients with atopic dermatitis [ 193 , 194 , 195 , 196 ]. There is currently a multi-center, double-masked, randomized, and placebo-controlled, parallel-group study that is evaluating the safety and efficacy of dupilumab in the treatment of signs and symptoms of individuals with atopic keratoconjunctivitis (NCT04296864).…”
Section: Therapeutic Targets For Immunobiologicsmentioning
confidence: 99%
“…Fukuda and colleagues reported that dupilumab was effective in treating giant papillae on the palpebral conjunctiva of two patients with atopic keratoconjunctivitis, and as such, they suggested the potential benefits of using dupilumab as an immunobiologic agent in individuals with severe forms of chronic ocular allergy [ 192 ]. However, there have been reports of dupilumab-associated ocular surface disease in patients with atopic dermatitis [ 193 , 194 , 195 , 196 ]. There is currently a multi-center, double-masked, randomized, and placebo-controlled, parallel-group study that is evaluating the safety and efficacy of dupilumab in the treatment of signs and symptoms of individuals with atopic keratoconjunctivitis (NCT04296864).…”
Section: Therapeutic Targets For Immunobiologicsmentioning
confidence: 99%
“…We performed an irrigation and washing of the CB, associated to the IOAB, as recommended in some studies (9,12). The use of SATB remains controversial (13,15,21,74,75). The slow growth of most common microorganisms isolated in CPE and their sequestration in the CB justify the need of repeated IOAB injection as we observed in cases n°3, 5, 6.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the identification of fungi using conventional techniques generally requires 3–7 days [ 6 ]. To improve identification, the use of molecular biology methods, such as real-time polymerase chain reaction (RT-PCR), for pathogen DNA quantification in specimens, can differentiate between true infection and possible contamination of the anterior chamber by microorganisms present in the conjunctival flora [ 7 , 8 , 9 , 10 ]. Moreover, the results of the PCR identification are available in less than 24 h [ 11 ].…”
Section: Introductionmentioning
confidence: 99%